Competition law and consumer protection - Cseres, Katalin Judit (Kluwer Law International The HagueNL, 2005)
Examines the role of competition law and consumer law in a free market economy; the notion of consumer welfare; and, the effect of the modernization of EC competition law for consumers. Looks at the economic theories of information, bounded rationally, and transaction costs; the special significance of vetical agreements and merger control; and, how consumers are affected by information asymmetries.